Tanggap Pertumbuhan dan Hasil Tiga Varietas Kacang Hijau terhadap Lama Genangan - Lestari, Sri Ayu Dwi; Wijanarko, Andy; Kuntyastuti, dan Henny (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
The objective of this research was to determine growth and yield responses of three mungbean varieties to waterlogging duration. The experiment was conducted at a screenhouse of ILETRI, Malang, East Java, from October to December 2016 using Alfisol soil from Probolinggo, East Java. The experiment consisted of two factors that were laid out in a factorial randomized complete block design with three replications. The first factor was mungbean varieties, namely Sriti, Vima 1, and Vima 2. The second factor was waterlogging durations, namely 0, 2, 4, and 6 days. The waterlogging treatments started at 20 days after planting. Mungbean plants fertilized with 250 kg Phonska ha-1 at the time of planting. The results showed that waterlogging treatments had negative effects on growth of the three varieties, indicated by a reduction in stem dry weight and leaf dry weight of the plants. Sriti variety was tolerant to waterlogging, Vima 1 was moderate tolerant, and Vima 2 was sensitive.Keywords: Alfisol soil, Vigna radiata, waterlogging stress